The epidemiology of trachoma in Eastern Equatoria and Upper Nile States, southern Sudan - Jeremiah Ngondi; Alice Onsarigo; Liknaw Adamu; Ibrahim Matende; Samson Baba; Mark Reacher; Paul Emerson; James Zingeser (The World Health Organization, 2005)
OBJECTIVE: Limited surveys and anecdotal data indicate that trachoma is endemic in the states of Eastern Equatoria and Upper Nile in southern Sudan. However, its magnitude and geographical distribution are largely unknown. We conducted surveys to ascertain the prevalence and geographical distribution of trachoma, and to identify targets for control interventions. METHODS: Population-based cross-sectional surveys were conducted in nine sites in southern Sudan between September 2001 and June 2004. Two-stage random cluster sampling with probability proportional to size was used to select the sample. Trachoma grading was done using the WHO simplified grading system. FINDINGS: A total of 17 016 persons were examined, a response rate of 86.1% of the enumerated population. Prevalence of signs of active trachoma in children aged 1-9 years was: TF = 53.7% (95% confidence interval (CI) = 52.1-55.3); TI = 42.7% (95% CI = 41.2-44.2); TF and/or TI = 64.1% (95% CI = 62.5-65.5). Prevalence of trichiasis (TT) in children aged less than 15 years was 1.2% (95% CI = 0.9-1.4), while TT prevalence in persons aged 15 years and above was 9.2% (95% CI = 8.6-9.9). Women were more likely to have trichiasis compared to men (odds ratio (OR) = 1.57; 95% CI = 1.34-1.84). Tentative extrapolation to the states of Eastern Equatoria and Upper Nile estimates that there is a backlog of 178 250 (lower and upper bounds = 156 027-205 995) persons requiring surgery and the entire population, estimated to be over 3.9 million, is in need of the SAFE strategy to control blinding trachoma. CONCLUSION: Trachoma is a public health problem in all nine of the study sites surveyed. The unusually high prevalence of active trachoma and TT in children points to the severity of the problem. There is urgent need to implement trachoma control interventions in trachoma endemic regions of southern Sudan.